The Cost of Acquiring Crossveinless-Ness in Waddington’s Assimilation - Ajay, Nair; Peter, K Dearden (Journal of Biotechnology and Biomedical Science, 2017)
Neo-Darwinian natural selection theory indicates that sudden, drastic changes in the environment place selective pressure on genetic variants in a population. As time progresses, this pressure sculpts individuals to better fit this new environment. Waddington’s classic experiment was repeated using white-eyed (the w1118strains) flies which produced the crossveinless (cve; disturbed wing crossveins) trait from the parent generation. The F1 generation was split into two selection lines: an Upward Selection Line, that produced more cve in successive generations, and a Downward Selection Line that responded with a consistent but non-linear decline in the percentage of crossveinless. This article will introduce and enlarge observations made on flies with cve; especially the manner in which the Waddington experiment impacts the population. It seems that Waddington evaluated crossveinless just by what it is good for, but not by the price of using it. That is to say, there is an inevitable cost that needs to be paid in order to acquire crossveinless-ness (cve and the associated phenotypes).
Keywords: Waddington; genetic assimilation; crossveinless; selection